Assessment of water level fluctuation impacts along River Nile, Egypt - Nasr Hekal; W.A. Fahmy (Water Science, 2023)
ABSTRACTThis paper aims to develop a computational model to assess and evaluate the annual water level fluctuation (WLF) impacts and their trends along any open channel (river, canal or lake) and provide reliable information that may help handle their implications. The impacts are related to water recession, flood plain areas, uncovered river bars and islands, locations of navigation bottle necks, and dredging works. The model is developed using Excel Spreadsheet VBA Coding. It computes the horizontal and inclined recession distances that govern water in take construction. It also computes the uncovered flood plain areas along the river reach to avoid encroachments and human interventions. In addition, it identifies the number of bar sand islands that emerge at low water levels to protect them against infringements. It also determines the locations of navigation bottle necks and computes the dredge volumes required. It can handle long river reaches quickly. Moreover, it is open-accessed where no hard locks or license renewals are required. It is run on Microsoft Excel which is an available and familiar environment to engineers. Therefore, the model can be a quick and powerful tool to support the decision-making process for projects related to such impacts, especially at the prefeasibility study stages. Reach '1' of River Nile in Egypt was taken as a case study to apply the model and show its capabilities in assessing the WLF impacts. This could help compute and analyze the size of the impacts and conceive their trends. Finally, the model could provide information about the impacts in concrete figures which can support decision making in coping properly with the impacts.